Gay life and culture : a world history - Aldrich, Robert, 1954- (London : Thames & Hudson, 2010)
From Theocritus' verses to 'Queer as Folk', from the berdaches of North America to the boy-wives of Aboriginal Australia, this book illustrates both the commonality of love and lust, and the various ways in which such desires have been constructed through the ages.
Includes bibliographical references and index.
boek